2011
DOI: 10.1016/j.jbankfin.2010.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the liquidity puzzle: Application of a new measure of the economic money stock

Abstract: Historically, attempts to solve the liquidity puzzle have focused on narrowly defined monetary aggregates, such as non-borrowed reserves, the monetary base, or M1. Many of these efforts have failed to find a short-term negative correlation between interest rates and monetary policy innovations. More recent research uses sophisticated macroeconomic and econometric modeling. However, little research has investigated the role measurement error plays in the liquidity puzzle, since in nearly every case, work invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…Several attempts to solve the liquidity puzzle include, inter alia, using nonborrowed reserves as an indicator for monetary policy (Eichenbaum 1992), extending the federal-funds VAR by including a proxy for the Fed's information about inflation (Sims 1992), considering non-borrowed monetary base shocks (Serletis and Chwee 1997), and using the federal-funds rate as an indicator of monetary policy actions (Bernanke and Blinder 1992). In this line of research, Kelly et al (2011) argue that the liquidity puzzle is due to measurement errors in narrowly defined monetary aggregates. Kelly et al then empirically find that the broadest monetary aggregate exhibits stronger liquidity effects.…”
Section: Liquidity Effectmentioning
confidence: 99%
“…Several attempts to solve the liquidity puzzle include, inter alia, using nonborrowed reserves as an indicator for monetary policy (Eichenbaum 1992), extending the federal-funds VAR by including a proxy for the Fed's information about inflation (Sims 1992), considering non-borrowed monetary base shocks (Serletis and Chwee 1997), and using the federal-funds rate as an indicator of monetary policy actions (Bernanke and Blinder 1992). In this line of research, Kelly et al (2011) argue that the liquidity puzzle is due to measurement errors in narrowly defined monetary aggregates. Kelly et al then empirically find that the broadest monetary aggregate exhibits stronger liquidity effects.…”
Section: Liquidity Effectmentioning
confidence: 99%
“…Kelly (2009) showed that this confounding causes simple-sum aggregates to fail to capture the true relationship between the economic money stock and interest rates. Finally, Kelly, Barnett, and Keating (2011) argues that much of the liquidity puzzle can be explained by the measurement error exhibited by simple-sum aggregation.…”
Section: Iwhmentioning
confidence: 99%
“…Conventional wisdom suggests that using a sufficiently narrow monetary aggregate is necessary to avoid the many empirical puzzles that have plagued monetary economists; however, Kelly, Barnett, and Keating (2011) finds that when money is measured using a reputable index number, a broad monetary aggregate exhibits empirical results that are more consistent with theoretical expectations than do narrow aggregates.…”
Section: Data and Descriptive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…''Rethinking the liquidity puzzle: Application of a measure of the economic money stock,' ' Kelly, Barnett and Keating (2011) provides a reconsideration of the potential solutions to the liquidity puzzle. They argue that historically attempts to solve this puzzle have focused on narrowly defined monetary aggregates, such as non-borrowed reserves, the monetary base, or M1.…”
mentioning
confidence: 99%